2015
DOI: 10.1002/alr.21588
|View full text |Cite
|
Sign up to set email alerts
|

Health utility outcomes in patients undergoing medical management for chronic rhinosinusitis: a prospective multiinstitutional study

Abstract: Background A health utility value represents an individual’s preference for living in a specific health state and is used in cost-utility analyses. This study investigates the impact of continuing medical therapy on health utility outcomes in patients with chronic rhinosinusitis (CRS). Methods The Medical Outcomes Study Short Form-6D (SF-6D) was administered to patients prospectively enrolled in a longitudinal study examining treatment outcomes for CRS. Patients were prescribed robust, initial medical therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 46 publications
3
50
2
2
Order By: Relevance
“…1131,1148,1342,1343,1345 These benefits were reflected in substantially greater QoL improvements as well as decreased used of antibiotics, oral corticosteroids, and reduced absenteeism in the group treated surgically. 43,1131,1148,1342,1343,1345 Finally, a modeling based economic evaluation demonstrates that an ESS strategy has a higher probability of being the more cost-effective intervention in patients with refractory CRS compared to continuing with medical therapy alone. 1346 The most recent Cochrane review highlights the lack of high-quality RCTs, which are insufficient to draw firm conclusions.…”
Section: Xf Surgery For Crswnp and Crssnp: Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…1131,1148,1342,1343,1345 These benefits were reflected in substantially greater QoL improvements as well as decreased used of antibiotics, oral corticosteroids, and reduced absenteeism in the group treated surgically. 43,1131,1148,1342,1343,1345 Finally, a modeling based economic evaluation demonstrates that an ESS strategy has a higher probability of being the more cost-effective intervention in patients with refractory CRS compared to continuing with medical therapy alone. 1346 The most recent Cochrane review highlights the lack of high-quality RCTs, which are insufficient to draw firm conclusions.…”
Section: Xf Surgery For Crswnp and Crssnp: Outcomesmentioning
confidence: 97%
“…46,49 Significant health utility improvements are seen with ESS and are comparable to those seen with joint replacement surgery and coronary angioplasty. 46,49,1340,1343 Comparative effectiveness studies of patients treated medically vs surgically can be divided into RCTs and real-world, nonrandomized observational comparison studies. A Cochrane Review in 2006 1130 based on 3 RCTs suggested that ESS did not offer additional benefit when compared to medical therapies.…”
Section: Xf Surgery For Crswnp and Crssnp: Outcomesmentioning
confidence: 99%
“…Significant improvement was reported in the surgical group in SF-6D values between baseline and 6-month follow-up, in contrast to the medical management and crossover groups, which showed no significant differences [51].…”
Section: Comparative Evidence Between Medical and Surgical Interventionsmentioning
confidence: 62%
“…Surgical patients reported greater improvements in disease-specific QOL measured by both the Chronic Sinusitis Survey and the Rhinosinusitis Disability Index [50] and had lower levels of ongoing antibiotic and steroid use and absenteeism [51]. Significant improvement was reported in the surgical group in SF-6D values between baseline and 6-month follow-up, in contrast to the medical management and crossover groups, which showed no significant differences [51].…”
Section: Comparative Evidence Between Medical and Surgical Interventionsmentioning
confidence: 94%
See 1 more Smart Citation